Reimagining Library Services: Transforming Libraries into Dynamic Learning Spaces in South African Universities - Noloyiso Nongalo (E-Journal of Humanities, Arts and Social Sciences)
This conceptual paper aimed to explore the transformation of university libraries in South Africa into dynamic learning spaces that cater to evolving academic and social needs of students. In the context of South Africa’s rapidly changing higher education landscape, where inclusivity and technological advancements are paramount, the role of university libraries is shifting from traditional information repositories to hubs of collaborative learning and student engagement. The paper employed a qualitative review of literature and an analysis of the existing infrastructures in libraries of Historically Disadvantaged Institutions (HDIs) to identify strategies for this transformation. The findings highlighted the pivotal role libraries play in promoting lifelong learning, enhancing digital literacy, and supporting academic success. Key recommendations include the integration of advanced technology, the creation of flexible, student-centred spaces, and the incorporation of inclusive practices to accommodate diverse student populations. This paper contributes to ongoing research by offering a model for reimagining library spaces in line with global trends, providing insights for other educational institutions seeking to foster dynamic, student-focused learning environments.